MEMAKMURKAN UMKM DESA SUMBERKERTO DENGAN PRODUKSI ES KRIM JAGUNG DAN KERIPIK SINGKONG - Anggita Oktaviana Putri (Jurnal Aksi Afirmasi, 2021)
UMKM (micro and middle entrepreneurship) plays an important role in advancing the economy of Sumberkerto villagers. In addition, UMKM is an alternative employment opportunity as well for people whose economically are quite adequate. Because the major population working as traditional farmers, agricultural products are not enough to meet their daily needs, villagers alternate the income by working outside. The potential of agricultural products and human resources can still be optimized with the presence of UMKM, encouraging students of Sumberkerto Group 2 Community Service Program to help overcome the above problems with training activities in making corn into ice cream. The targets of the community service activities are Sumberkerto village residents, in Pagak District of Malang Regency. The method of approach is carried out by field surveys, interview with local residents for planning and training programs in making corn ice cream. The products manufactured besides corn ice cream are UMKM training and bazaar at IAI Al-Qolam and the sustainability methods of training on corn ice cream product for Sumberkerto villagers.